Fiscal policy during the transition in Eastern Europe - Roger H. Gordon (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The paper tries to provide an overview of the fiscal pressures on Eastern European governments during the transition from centrally planned to market economies, and what responses might be called for. In each case it is started by describing the conventional wisdom concerning how best to deal with such pressures in a developed market economy. Eastern European countries are not developed market economies, however, so the implications of various idiosyncratic features of these economies for fiscal policy are also discussed. Given the lack of experience and research on economies undergoing such a economic transition, these latter arguments are inevitably somewhat speculative.
Keywords: 330